Students' perceptions of a constructivist classroom: A collaborative learning approach - Leow, Fui-Theng; Neo, Mai (2013)
Today’s classroom no longer has four walls and students no longer sit in a row to learn from a subject expert. Technologies and web 2.0 tools have walked into the classroom, and learning now happens everywhere and anytime through collaboration, sharing and reflection between the peers. These changes have connected the students, educators, learning resources and activities into a collaborative learning environment that allow students to personalize the learning process, and change the sole determining role of the educators. Therefore, it builds the student-centred learning experience and makes the classroom learning to be less teacher-dependent. This research aims at studying students’ perception on web-based collaborative learning in constructivist learning environment which is designed based on Jonassen’s constructivist learning principle (Jonassen, 1999). In addition, web 2.0 social applications are used to engage the students in this learning approach to promote participation, collaboration and communication along the learning process. The research question in this study is what is the students’ perception on web-based collaborative learning in a constructivist learning environment? This research study involves 104 Degree year 1 students as the research samples. They are exposed to the constructivist learning environment which is embedded in a common subject that offered to all IT Degree students who at INTI International University. This constructivist learning environment is centred at a student project of developing an interactive multimedia application which requires students to use various skills, software tools, and approaches to solve the ill-structure problems. Students needed to work in a group collaboratively to handle this project as it has a large scope, complex requirements and limited time. In the project development stages, students need to complete several tasks both individually and collaboratively, which includes project proposal, background study, planning and progress report, content sharing and discussion. All these tasks are done with the peer interaction through the use of various web 2.0 social tools, which are wiki, blog, social networking site. A set of questionnaire is used to collect the student perceptions on the group collaborative learning in the constructivist learning environment. This survey is conducted once the completion of the project and the result is then analyzed by using SPSS to assess the reliability of the survey items, and to perform factor analysis. These statistical data is used to uncover some meaningful facts and its underlying relationships, and subsequently, enhances the understanding on how students perceive web-based collaborative learning in this setting. Furthermore, the analyzed facts become the input to study the impact on the learning experience and the attitude change in a constructivist learning environment with multimedia and web 2.0 social tools. It is expected that the outcome of this research study emphasizes on presenting the important factors in designing the learning environment which aims to enhance the effectiveness in collaborative learning.